(A-LIEP 2011)Exploring the Skills and Competencies of Information Professionals for Knowledge Management in the Information Institutions of Bangladesh / Md. Abul Kalam Siddike and Md Shiful Islam - Siddike, Md. Abul Kalam; Islam, Md Shiful (2011)
The aim of the study is to explore the views of information professionals for knowledge management (KM) in the libraries/information institutions of Bangladesh. Research Questions-This paper seeks to address the following research questions: How the information professionals of Bangladesh perceive the views of KM? What are likely to be the skills required by the information professionals of Bangladesh for KM in the libraries of Bangladesh? and what are likely to be the critical success factors for encouraging KM in the information institutions of Bangladesh? The methodology includes a quantitative approach. The study has been conducted through a survey using a pre-structured questionnaire. A short and structured questionnaire was sent to 50 information professionals who had been working in different libraries of Bangladesh through email and/or by post. The respondents were selected from 6 divisions of Bangladesh (25 respondents from Dhaka division, 5 each in Chittagong, Rajshahi, Khulna, Barishal and Sylhet division). We received 30 responses, for a response rate 60%. The results of the study show that that 93.24% of the respondents first read about KM in the literature, but none had taken any courses on KM. Only 6.76% of the respondents had attended a workshop on KM. Findings also yield that most of the professionals believe that communication skills, facilitation skills, coaching skills, mentoring skills, networking skills, negotiating skills, consensus building skills and team working skills are inevitable for KM in the libraries of Bangladesh. This paper also suggests some critical success factors for encouraging the information professionals to KM in the libraries of Bangladesh. It investigates the original views of the library and information professionals of Bangladesh regarding the skills and competences of information professionals for KM in the libraries of Bangladesh. The department of Information Science and Library Management of Dhaka University and Rajshahi University should introduce KM course(s) either in the graduate level or in the post-graduate level